Biological control as the primary option in sustainable pest management: the cassava pest project - Herren, H.R. (1990)
The cassava mealybug (CM), Phenacoccus manihoti Matile-Ferrero was unknown to science when it was first discovered in 1973, along the Congo-Zaire river in Central Africa. In 1981, following inten¬ sive exploration and taxonomie studies, CM was found to have originated from a limited area of South America, from where it was accidentally introduced to Africa in the late 1960s or early 1970s. In 1971, the cassava green mite (CGM), Mononychellus tanajoa (Bondar) was discovered in Uganda; it has its origin also in South America. Since then, the pests have spread over most of the cassava belt of Africa, threatening to destroy cassava, the staple food crop of some 200 million Africans. Classical biological control through the use of exotic natural enemies, provides the basis for an economically viable and environmentally sound solution. Also, this approach is particulary, but not exclusively, appropriate for low-input, subsistence agricultural systems since it requires little or no intervention by individual farmers or agricultural extension services. The extreme urgency of the problem, with its attendant threat of widespread famine, called for an unprecedented level of or¬ ganization and international cooperation. Exploration, ecological and biological studies of natural enemies, the development of appropriate mass-rearing and distribution technologies, and a major program of manpower training, were undertaken through the formation of an extensive network of scientific collaborators in Africa, Europe and the Americas. Finally, follow-up studies, underpinned by the development of a simulation model and a benefit/cost analysis, have demonstrated that classi¬ cal biological control, properly planned and implemented, can provide a timely, cost effective and ecologically safe solution to a major pest problem.